Aesthetic Testimony and the Norms of Belief Formation. (6th March 2013) - Robson, Jon
Abstract Unusability pessimism has recently emerged as an appealing new option for pessimists about aesthetic testimony—those who deny the legitimacy of forming aesthetic beliefs on the basis of testimony. Unusability pessimists argue that we should reject the traditional pessimistic stance that knowledge of aesthetic matters is unavailable via testimony in favour of the view that while such knowledge is available to us, it is unusable. This unusability stems from the fact that accepting such testimony would violate an important non‐epistemic norm of belief formation. In this article I present an objection to unusability pessimism and argue that Robert Hopkins, the view's most prominent defender, fails to motivate adequately the claim that there are such non‐epistemic belief norms. The cases which putatively legitimize usability norms can be explained by appeal to more familiar norm types: epistemic norms of belief formation, and non‐epistemic norms which govern action other than belief formation. The intent of this article is not primarily negative, however, and I will also argue that understanding why the unusability position fails helps us to identify a promising new direction for the pessimist's opponents who wish to defend the legitimacy of forming aesthetic beliefs on the basis of testimony.